A study of the effect of brand on profitability in the industry - Pirayesh, Reza (Opción, 2019)
In this study brand equity will be evaluated comparatively as an effective factor between the bank and insurance firms which are accepted in Tehran stock exchange from 2009-2015. This research is practical based on its goal, is descriptive based on the methods that have been done by correlation and regression. The results show that the impact of brand equity on profitability in banks is more than insurance firms. As a conclusion, managers should use promotional tools such as public relations and media interviews to introduce their services and try to strengthen their affiliates by strengthening their brand value